Production of Bioorganic Liquid Fertilizer from Food Waste for Chilli Plants - Ayob, Adlina Aqilah; Hamzah, Nurul Hamizah; Rosli, Siti Nordiana Sahira; Abu Bakar, Norhaliza (Multidisciplinary Applied Research and Innovation, 2025)
The widespread use of inorganic fertilizers in chili pepper (Capsicum annuum L.) farming raises environmental concerns. This study explores a sustainable alternative: a bio-organic liquid fertilizer produced through the fermentation of food waste (eggshells, spent coffee grounds and banana peels). These food wastes are rich in essential plant nutrients, namely nitrogen (N), phosphorus (P), and potassium (K), which are critical for optimal chili pepper growth. The research investigates the impact of varying fertilizer concentrations on plant growth. Weekly measurements of plant height, average leaf width, and stem diameter assessed the effectiveness of the fertilizer. The findings suggest that the bio-organic fertilizer, particularly at higher spent coffee ground concentrations (known for high NPK content), significantly promotes chili plant growth compared to traditional methods. This research promotes an environmentally friendly approach to chili pepper farming by diverting food waste from landfills and reducing reliance on inorganic fertilizers.